Salvia miltiorrhiza polysaccharide and its related metabolite 5-methoxyindole-3-carboxaldehyde ameliorate experimental colitis by regulating Nrf2/Keap1 signaling pathway. (15th April 2023) - Fu, Yu-Ping; Peng, Xi; Zhang, Chao-Wen; Jiang, Quan-Xing; Li, Cen-Yu; Paulsen, Berit Smestad; Rise, Frode; Huang, Chao; Feng, Bin; Li, Li-Xia; Chen, Xing-Fu; Jia, Ren-Yong; et al.
Abstract: The roots of Salvia miltiorrhiza have been used in Traditional Chinese Medicine for thousands of years. However, tons of aerial parts of this plant are usually discarded in the production of roots preparation. To make better use of these plant resources, the polysaccharide isolated from the aerial part of S. miltiorrhiza was investigated for its potential protection against intestinal diseases. A pectic polysaccharide (SMAP-1) was isolated and characterized being composed of homogalacturonan as the main chain and rhamnogalacturonan type I as ramified region, with side chains including arabinans and possible arabinogalactan type I and II. SMAP-1 exhibited robust protective effects against dextran sodium sulfate (DSS)-induced colitis and restored colitis symptoms, colonic inflammation, and barrier functions. Anti-oxidative effects were also observed by up-regulating Nrf2/Keap1 signaling pathway. Additionally, the level of serum 5-methoxyindole-3-carboxaldehyde (5-MC) was restored by SMAP-1 identified in metabolomic analysis, being correlated with the aforementioned effects. Protection against oxidative stress on intestinal porcine enterocyte cells (IPEC-J2) by 5-MC was observed through the activation of Nrf2/Keap1 system, as also shown by SMAP-1. In conclusion, SMAP-1 could be a promising candidate for colitis prevention, and 5-MC could be the signal metabolite of SMAP-1 in protecting against oxidative stress in the intestine. Graphical abstract: Unlabelled Image